Muslim Mukalaf Menurut Kiai Hasan Dimejo (Analisis Pragmatik pada Manuskrip Haqqul Islam) - Ningsih, Iin Surya; Khasanah, Aniswatun (Perpustakaan Nasional RI, 2023)
This research examined the Haqqul Islam (HI) manuscript by Kiai Hasan Dimejo. The manuscript belongs to KH. Amin Ridlo and is stored in the Manbaul Anwar Islamic Boarding School, Krasak Mojotengah Village, Wonosobo. The manuscript has been digitized and can be accessed through the website https://lektur.kemenag.go.id/ with the collection code LKK_WONOSOBO2015_MAR04. Apart from editing the text of Haqqul Islam, this research aims to explain the obligations of mukalaf Muslims according to the views of Kiai Hasan Dimejo. Apart from that, it was stated that the contents of the manuscripts were considered important because they contained a description of the flow of Islamic preaching during the pre-independence period and were the beginning of the birth of the oldest Islamic congregation in Indonesia. This research was conducted using descriptive and qualitative methods. The contents of the text were analyzed by referring to the theory of philology to describe the content of the text and combined with Abrams's pragmatic approach to reveal the values contained in the text. There are 21 points on the obligations of Muslim Mukalaf, according to Kiai Hasan Dimejo in this manuscript. Through analysis using the pragmatic approach of the Abrams model, it can be concluded that the HI manuscript contains five nuances of meaning, namely nuances of religious meaning, nuances of educational meaning, nuances of social meaning, nuances of linguistic meaning, and nuances of doctrinal meaning. The results of this research are in the form of information for the public and also make it easier for them to understand and apply the teachings contained in the HI manuscript regarding the obligations of a Muslim Mukalaf.